National values in publicistic works of M.Dulatov - Tapanova, C.Е.; Umbetova, А.Қ. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2023)
The study of the journalistic works of Alash veterans is not only the main task of today, but also necessary for us to look into our past, analyze our present and guide our future. This task is especially important for our country, which lives in modern conditions of independence and is becoming known to the world. Mirzhakip Dulatov was an educator of the Kazakh people, who held a democratic orientation. In addition to his poetic manifesto" Oyan, Kazakh", he developed a new methodology for the textbook of Kazakh literature and presented a new project for teaching in national schools. His ideas took the development of the Kazakh people to a new stage. Mirzhakip Dulatov's work is distinguished by its versatility. He is a poet, a master of speech. He is a person who saw all the hardships of a turbulent period and loved his nation very much. Therefore, we tried to consider Mirzhakyp Dulatov's work in the framework of that period, in unity with the political and cultural environment, as a whole.